If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1c(5) + -23 = -18 Reorder the terms for easier multiplication: -1 * 5c + -23 = -18 Multiply -1 * 5 -5c + -23 = -18 Reorder the terms: -23 + -5c = -18 Solving -23 + -5c = -18 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + -5c = -18 + 23 Combine like terms: -23 + 23 = 0 0 + -5c = -18 + 23 -5c = -18 + 23 Combine like terms: -18 + 23 = 5 -5c = 5 Divide each side by '-5'. c = -1 Simplifying c = -1
| x+16=2x+4 | | x+16=2x+3 | | 48+3w+10w=100 | | (8x^2)+(3x^2-2)= | | -3q^2+30q-48=0 | | 3x-90=46 | | 2x+6=2(x-8)+10 | | 4x^2-9y^2-16x-18y=29 | | m+(-13)=(-18) | | 293=3x | | 4/5/17+y=6/16/17 | | x=-3y+17 | | 4y^2+16y+21= | | y=3.5x+6.1 | | -6(3x-6)=120 | | -23=2x+3(-x-4) | | -2=-15-x | | 6z+24=6z+4 | | 6y-4-3y+1= | | 4(2m+1)=36 | | 2/3n+3=9 | | 14+5x=3(-3x+3)-11 | | 7k+5=4k-19 | | 6n-8=16 | | 2k-4=(-8) | | 3Z+6=15 | | m^2-16m-11=0 | | -8u+6(u+6)=20 | | 6s+34=6+4(2s+4) | | x^2-6x+104=4 | | 256=8(4x+12) | | z+13.53=2.53 |